2018
DOI: 10.5964/ejop.v14i2.1418
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of knowing in metacognitive monitoring: Effects of the type of information and of personal, cognitive, metacognitive, and individual psychological characteristics

Abstract: The aim of the paper is to analyse the illusion of knowing in metacognitive monitoring of the learning activity of university students (n = 262). The analysis focuses on the effects of the different types of information proposed and of personal, cognitive, metacognitive, and individual psychological characteristics of the participants. The research has shown that the illusion of knowing can occur in all types of metacognitive judgments, but is more evident in prospective judgments and depends on the type of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 64 publications
(112 reference statements)
4
23
0
2
Order By: Relevance
“…Thus, our findings are consistent with those illustrating a positive correlation between self-efficacy and academic achievement (Pintrich et al, 1993;Zeegers, 2004). However, they are inconsistent with those of Avhustiuk et al (2018), who found that students' general self-efficacy increased with the accuracy of self-assessment. In an earlier study (Al Kuhayli et al, 2019), involving a larger group of students with a teacher-centered educational past, we found no link between general self-efficacy and measures of self-assessment and performance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, our findings are consistent with those illustrating a positive correlation between self-efficacy and academic achievement (Pintrich et al, 1993;Zeegers, 2004). However, they are inconsistent with those of Avhustiuk et al (2018), who found that students' general self-efficacy increased with the accuracy of self-assessment. In an earlier study (Al Kuhayli et al, 2019), involving a larger group of students with a teacher-centered educational past, we found no link between general self-efficacy and measures of self-assessment and performance.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, the illusion of knowing phenomenon, which is a common judgment of overestimation of one’s knowledge, understanding, and/or competence is to be prevented at all costs ( Dunning, Heath, & Suls, 2004 ; Glenberg, Wikinson, & Epstein, 1982 ). Second, learners must be willing and able to use strategically information about their knowledge, understanding, and competence to modulate thought and action during learning and testing ( Avhustiuk, Pasichnyk, & Kalamazh, 2018 ).…”
mentioning
confidence: 99%
“…Our findings suggest that self-efficacy contributes substantially to students' inaccurate predictions of their exam grades as well as to their confidence in the predictions made. Avhustiuk et al [44], however, found that students' general self-efficacy increased with the accuracy of self-assessment, whereas Al Kuhayli et al [45] did not find any relationship. It has been suggested that hope and self-efficacy are overlapping constructs [46].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, mixed evidence also exists from the Western world regarding whether general self-efficacy contributes to the accuracy of students' performance estimations and subjective confidence. Avhustiuk et al (2018) found that students' general self-efficacy increased with the accuracy of self-assessment, whereas Hamann et al (2020) reported that it contributed to inaccuracies of self-assessment and to the confidence with which students made estimates. In the Middle East, Al and Pilotti et al (2019) reported no relationship between general selfefficacy and estimation accuracy or confidence.…”
Section: Introductionmentioning
confidence: 97%
“…Of course, desirable performance begins well before the actual task is executed. It derives from the learners' ability to accurately estimate their performance on the upcoming task (metacognitive awareness) as well as their commitment to engage in corrective actions (metacognitive control) if the degree of discrepancy between desired and predicted performance is significant (Avhustiuk et al, 2018). Consider, for instance, students who are preparing for a test.…”
Section: Introductionmentioning
confidence: 99%